Mechanisms and outcomes of metabolic surgery in type 2 diabetes - Mansor, Fazliana; Nor Hanipah, Zubaidah (MDPI AG, 2022)
This review is aimed at synthesizing the mechanisms and outcomes of metabolic surgery on the endocrine system, microbiome, metabolomics, and at the molecular level. We review the hormonal, adipokine, microbiota, microRNA, and metabolomic changes in human and animal models following metabolic surgery for the treatment of obesity and diabetes. The most relevant studies in this area over the past 17 years have been considered for this review. In most cases, metabolic procedures, especially those that include intestinal bypass components, showed the remission of type 2 diabetes. This involves a variety of weight-independent mechanisms to improve glucose homeostasis, improving insulin sensitivity and secretion, gut microbiota, and bile acid cross-talk.